ОГЛЯД СУЧАСНИХ ПІДХОДІВ ДО РОЗРОБКИ НАНОЛІКІВ (World Science, 2020)
The article deals with nanopharmacy, a new medical discipline that combines chemistry, physics and engineering to develop nanoscale systems used in diagnosis and therapy. The use of nanoparticles for the development of new nanodrugs requires a deep understanding not only of the properties of nanomaterials, but also of the pathophysiology of diseases. Nanopharmacy help solve complex problems associated with improving the effectiveness of existing therapeutic agents and the use of nanomaterials in the manufacture of nanodrugs.